2020
DOI: 10.15698/mic2020.11.735
|View full text |Cite
|
Sign up to set email alerts
|

Novobiocin inhibits membrane synthesis and vacuole formation of Enterococcus faecalis protoplasts

Abstract: We demonstrate that plasma membrane biosynthesis and vacuole formation require DNA replication in Enterococcus faecalis protoplasts. The replication inhibitor novobiocin inhibited not only DNA replication but also cell enlargement (plasma membrane biosynthesis) and vacuole formation during the enlargement of the E. faecalis protoplasts. After novobiocin treatment prior to vacuole formation, the cell size of E. faecalis protoplasts was limited to 6 μm in diameter and the cells lacked vacuoles. When novobiocin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Our previous studies showed that E. faecalis protoplast enlargement requires DNA replication ( Kami et al., 2019 ; Tsuchikado et al., 2020 ). DNA attachment to the plasma membrane ( Earhart et al., 1968 ; Leibowitz and Schaechter, 1975 ; Marvin, 1968 ; Sueoka and Quinn, 1968 ) might be needed for enlargement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that E. faecalis protoplast enlargement requires DNA replication ( Kami et al., 2019 ; Tsuchikado et al., 2020 ). DNA attachment to the plasma membrane ( Earhart et al., 1968 ; Leibowitz and Schaechter, 1975 ; Marvin, 1968 ; Sueoka and Quinn, 1968 ) might be needed for enlargement.…”
Section: Resultsmentioning
confidence: 99%
“…The E. faecalis protoplast enlargement requires DNA replication ( Kami et al., 2019 ; Tsuchikado et al., 2020 ). Thus, when DNA replication stops, cell enlargement also stops.…”
Section: Introductionmentioning
confidence: 99%